Mass Spectrometric Determination OF Radioactive Decay OF 87Rb TO 87Sr IN Some Iraqi Geological Minerals - Hussain, K. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Determination of isotopic composition of strontium and Rubidium in some geological samples was performed by using thermal ionization mass spectrometry. The optimum evaporation and ionization currents were determined for each of strontium and Rubidium, employing double rhenium filament by using faraday cup as detector. The results were compared  with  reference  mater ials (NBS Standards) of Sr and Rb. Theradioactive decay of 87Rb to 87Sr was also determined.